Energy transition and behavioural change in rural areas - The role of energy cooperatives - Timo Kaphengst; Eike Karola Velten (WWWforEurope, 2014)
The overall aim of this study is to investigate energy transition processes in rural areas by paying particular attention to the role of energy cooperatives in these processes. The study should mainly uncover, if and under which conditions energy cooperatives provide favourable structures for initialising transition processes in rural areas and involving relevant stakeholders. A particular focus will be on the question of agency in energy transition processes and the internal drivers and motivations of the people to become involved in energy cooperatives. The theoretical background of the study is the transition theory and transition management (TM) concept, which we complement by drawing on Practice Theory and social learning in order to explain behavioural changes. The study mainly builds on an empirical case study in the Rhön-Grabfeld district in Northern Bavaria (Germany). Several energy cooperatives were formed there recently through the support and promotion a small rural consultancy. In addition, the results from the case study will be complemented by and compared with other case studies from Denmark and Spain taken from the literature. One of the main research question will be, to what extent energy cooperatives can be considered a good practice example for participatory involvement in transition processes and to what extent does this have an influence on the inner drivers/motivations of actors in this transition, possibly leading to behavioural changes.
Keywords: D83; Q01; Q28; 330; Academic research; Behavioural economics; Post-industrialisation; Social development; Social innovation; Socio-ecological transition; Transition research